Functional and anatomical outcomes after successful repair of macula‐off retinal detachment: a 12‐month follow‐up of the DOREFA study. Issue 7 (11th February 2021) - Baudin, Florian; Deschasse, Clémence; Gabrielle, Pierre‐Henry; Berrod, Jean P.; Le Mer, Yannick; Arndt, Carl; Tadayoni, Ramin; Delyfer, Marie N.; Weber, Michel; Gaucher, David; Saleh, Maher; Chiquet, Christophe; et al.
Abstract: Purpose: To report visual and anatomical outcomes and determine predictors of good visual acuity (VA) recovery after macula‐off rhegmatogenous retinal detachment (RD). Methods: Prospective multicentre study including 115 eyes from 115 patients successfully operated on for RD, with assessment of VA and spectral‐domain optical coherence tomography (SD‐OCT) macular images at 1, 3, 6 and 12 months after surgery. Results: Over the follow‐up period, VA significantly improved from median [IQR] 62 [46; 72] ETDRS letters at 1 month to 75 [67; 80] ETDRS letters at 12 months (p < 0.001) with a concomitant decreased number of eyes with any SD‐OCT lesions (p < 0.001). The presence of subretinal fluid (SRF) significantly decreased (p < 0.001), as did the number of photoreceptor (PR) layer lesions (p = 0.04). At 12 months, lesions in the PR layer and poor VA recovery were significantly associated with a longer time to surgery (p = 0.007 and p < 0.001, respectively). The rate of patients without PR lesions increased from 40.9% at 1 month to 60.0% at 6 months and 73.9% at 12 months (p < 0.001). The incidence of epiretinal membrane (ERM) significantly increased (p < 0.001), while cystoid macular oedema (CME) remained stable over time. Visual acuity (VA) at 3 months postoperatively was a good reflection of final VA recovery (p < 0.001). Conclusion: Visual acuity (VA) improved in parallel with the decreasing number of eyes with SD‐OCT lesions after macula‐off rhegmatogenous RD. A long time to surgery was the only preoperative factor associated with poor VA recovery after retinal detachment surgery.